2010
DOI: 10.1111/j.1574-6968.2010.02116.x
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium solani is responsible for mass mortalities in nests of loggerhead sea turtle, Caretta caretta, in Boavista, Cape Verde

Abstract: The fungus Fusarium solani (Mart.) Saccardo (1881) was found to be the cause of infections in the eggs of the sea turtle species Caretta caretta in Boavista Island, Cape Verde. Egg shells with early and severe symptoms of infection, as well as diseased embryos were sampled from infected nests. Twenty-five isolates with similar morphological characteristics were obtained. Their ITS rRNA gene sequences were similar to the GenBank sequences corresponding to F. solani and their maximum identity ranged from 95% to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
98
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 25 publications
6
98
1
3
Order By: Relevance
“…Various Fusarium spp. have been reported to cause disease of prawns (Khao et al 2005), tiger prawn (Khao et al 2004), infections of the eggs of loggerhead sea turtle (Sarmiento-Ramirez et al 2010), Aphanomyces sinensis infections of juvenile soft-shelled turtle (Takuma et al 2011) and various fungi causing skin infections of southern right whale (Reeb et al 2011). Algae susceptible to fungal infections include: the red algae Bangia, Palmaria, Polysiphonia and Porphyra (Pueschel and Vandermee 1985;Müller et al 1999;Sekimoto et al 2008a, b), and the brown algae Cystoseira, Halidrys, and Pylaiella (Alongi et al 1999;Gachon et al 2006;Harvey and Goff 2010).…”
Section: Marine Fungi On Animal Hostsmentioning
confidence: 97%
“…Various Fusarium spp. have been reported to cause disease of prawns (Khao et al 2005), tiger prawn (Khao et al 2004), infections of the eggs of loggerhead sea turtle (Sarmiento-Ramirez et al 2010), Aphanomyces sinensis infections of juvenile soft-shelled turtle (Takuma et al 2011) and various fungi causing skin infections of southern right whale (Reeb et al 2011). Algae susceptible to fungal infections include: the red algae Bangia, Palmaria, Polysiphonia and Porphyra (Pueschel and Vandermee 1985;Müller et al 1999;Sekimoto et al 2008a, b), and the brown algae Cystoseira, Halidrys, and Pylaiella (Alongi et al 1999;Gachon et al 2006;Harvey and Goff 2010).…”
Section: Marine Fungi On Animal Hostsmentioning
confidence: 97%
“…2c) can lead to host extirpation because their growth rate is decoupled from host densities and many fungal diseases threatening natural populations are caused by opportunistic fungi with long-lived environmental stages. Many fungi in the phylum Ascomycota are common soil organisms and are tolerant of salinity with the consequence that, when they enter the marine system through freshwater drainage, they are able to infect susceptible hosts such as corals ( A. sydowii 42 ), sea otters ( Coccidioides immitis 43 ) and the nests of loggerhead turtles ( Fusarium solani 44 ). In terrestrial environments, potentially lethal fungi are ubiquitous, such as the causative agent of aspergillosis, Aspergillus fumigatus , and soil surveys have shown that Geomyces spp.…”
Section: Fungal-disease Dynamics Leading To Host Extinctionmentioning
confidence: 99%
“…Females dig nest chambers on the beach, and after oviposition they cover their eggs, camouflage the nest site and return to the ocean. During incubation, eggs are exposed to several threats that can cause a significant embryo mortality (Ditmer and Stapleton, 2012) such as beach flooding or erosion (Van Houtan and Bass, 2007;Wood et al, 2000), infections produced by microorganisms (Phillott and Parmenter, 2001;Sarmiento-Ramírez et al, 2010), poaching (Frazier, 1980;Hope, 2002), natural predation (Dodd, 1988;Donlan et al, 2004;Fowler, 1979) and even expected redundant impacts by off-road vehicles (ORVs) on sandy beaches (Schlacher et al, 2008). Carnivore mammals are considered the most important turtle nest predators (Ratnaswamy and Warren, 1998), and the regulation of mammalian carnivores (e.g.…”
Section: Introductionmentioning
confidence: 99%